2017
DOI: 10.1080/10503307.2017.1315779
|View full text |Cite
|
Sign up to set email alerts
|

Building emotional resilience over 14 sessions of emotion focused therapy: Micro-longitudinal analyses of productive emotional patterns

Abstract: Examining successful treatment cases showed several theoretically coherent kinds of temporal patterns, although not always in the same case. Clinical or methodological significance of this article: This is the first paper to demonstrate systematic temporal patterns of emotion over the course of an entire treatment. (1) The study offers a proof of concept that longitudinal patterns in the micro-processes of emotion can be objectively derived and quantified. (2) It also shows that patterns in emotion may be iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…A typical assumption in psychotherapy research is that change is gradual and linear, but individual time course data has revealed that the process of psychotherapy can also follow a nonlinear course [ 11 ]. Change in symptoms and therapy processes can show quadratic patterns (U- or V-shaped [ 76 ]), as well as cubic [ 77 , 78 ], saw-toothed [ 79 , 80 ], and other nonlinear patterns [ 81 – 83 ], all of which have been associated with better treatment outcomes. In addition, specific types of discontinuities or sudden jumps in time course data have been identified that predict symptom reduction across a variety of clinical disorders, including the sudden gain [ 74 , 84 86 ] (a large decrease in symptoms in a 1-week interval), the depression spike [ 78 ] (an intentionally induced and transient symptom exacerbation), and the cusp catastrophe pattern, which has been used to model sudden transitions from an abstinent state to relapse in addiction research [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…A typical assumption in psychotherapy research is that change is gradual and linear, but individual time course data has revealed that the process of psychotherapy can also follow a nonlinear course [ 11 ]. Change in symptoms and therapy processes can show quadratic patterns (U- or V-shaped [ 76 ]), as well as cubic [ 77 , 78 ], saw-toothed [ 79 , 80 ], and other nonlinear patterns [ 81 – 83 ], all of which have been associated with better treatment outcomes. In addition, specific types of discontinuities or sudden jumps in time course data have been identified that predict symptom reduction across a variety of clinical disorders, including the sudden gain [ 74 , 84 86 ] (a large decrease in symptoms in a 1-week interval), the depression spike [ 78 ] (an intentionally induced and transient symptom exacerbation), and the cusp catastrophe pattern, which has been used to model sudden transitions from an abstinent state to relapse in addiction research [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pascual-Leone and Greenberg [43] demonstrated that the achievement of the emotional states in the AMM category proceeded in the occurrence of the emotional states present in the EED category. Also, in research using this model in a therapeutic context, the presence of sequential links between various states is demonstrated, regardless of the type of therapeutic modality applied [44,45,48,61]. Complementarily, Welling [47] reflects on the importance of the transformative emotional sequence as a common therapeutic principle of change, reinforcing the idea of the need for a prior activation of a problematic emotional state, followed by the activation of adaptive emotional states.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, the presence of this effect in the AMM-EED Sequence also aligns with some ideas expressed in the literature. Pascual-Leone [48] stated that no study has yet been able to establish links that simultaneously unify all the emotional states present in the sequential model. Moreover, and as previously mentioned, the sequence of emotional states present in the sequential model is nonlinear, only being necessary to experience all emotional states to reach the higher level of emotional processing [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A narrative account of how client change occurred over the course of therapy helps illustrate the sequential process of emotion. This case, which was part of a clinical trial of EFT (Greenberg, Warwar, & malcolm, 2008), was also featured in a recent study on the client's emotional progress over time (Pascual-Leone, Yeryomenko, Sawashima, & Warwar, 2017). 1 Jeff was a 50-year-old lawyer who had been married for 15 years and had a 12-year-old daughter.…”
Section: Sequential Model Of Emotional Processingmentioning
confidence: 99%